Isolation and Identification of Biosurfacting Bacteria from the Contact Pond of WWTP Palm Oil Industry Pond - Raynaldo Empindonta Sembiring; M. Hasbi M. Hasbi; Budijono Budijono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractBiosurfactants are surfactants produced by bacteria capable of degrading oil in water. This study aims to obtain bacteria that can produce biosurfactants from the Contact Pond of IPAL palm oil industry PT. Eka Dura Indonesia, Kota Lama, Rokan Hulu Regency, which was held from April to July 2019. The procedure for the implementation, first, the sample was diluted and enriched using BHI (Brain Heart Infusion) media for 24 hours. Based on the results of the study found 3 isolate of bacteria. The three bacteria are bacteria that can produce bio surfactants with an emulsification index of Isolate D1 41.81%, Isolate D2 43.6%, and Isolate D3 32.72%. Keywords: Bio surfactants, Proteus vulgaris, Proteus mirabilis, and Enterobacter aerogenes